The Strategic Development Model of Organizational Dynamic Capabilities at Private Higher Education Institutions Using Soft System Methodology - Muhammad Yusuf S Barusman (UBL, 2013)
Today, Indonesian private higher education institutions (IPHEIs) are facing enormous challengesregarding their existences due to dynamic environment such as competition, changing governmentpolicies, demanding needs of industries etc. Contradictory among such institutions in responding to thedynamic environment is interesting topic to study. The objectives of this paper are three folds, first is todescribe the use of Soft System Methodology as an epistemological bases in facing such a complex,dynamic problems. The second is to build institutional model of private higher education institutionsustainability. The third is to develop the strategic model of organizational dynamic capabilities ofprivate higher education institutions. The result of this study shows that there are 21 stakeholders thatinfluence the sustainability of private higher education institutions. In addition, the institutional model ofprivate higher education and the strategic model of organizational dynamic capabilities at private highereducation institution describe the process of coordinating, learning, and reconfiguring the private highereducation institution stakeholders.